Analysis of Psychological Well-Being and Social Support on Employee Performance Through Job Satisfaction at BPR Bank Gresik - Kurniawan, Kurniawan; Dewi Yustiana; Koen Irianto Uripan; Sutoyo, Sutoyo; Farij Ibadil Maula (Jurnal Ekonomi, 2025)
This study aims to analyze the influence of psychological well-being and social support on the performance of BPR Bank Gresik employees, with job satisfaction as a mediating variable. The population in this study were 100 employees at BPR Bank Gresik, with the sampling technique using a census, so the sample obtained was the same number as the population, namely 100 employees of BPR Bank Gresik. Testing was carried out using Partial Least Squares (PLS) analysis to examine the relationship between variables. The results of the study showed several main findings. First, psychological well-being has a positive contribution in improving employee performance. Second, social support contributes in encouraging employee performance by creating an atmosphere that motivates them to show their best potential, including in efforts to obtain the desired position. Third, psychological well-being also has a positive effect on performance through job satisfaction. Fourth, social support has a significant contribution in improving performance through job satisfaction